Comparing the Effectiveness of Doing Intra-uterine Insemination 36 and 42 Hours After Human Chorionic Gonadotropin (HCG) Injection on Pregnancy Rate: A Randomized Clinical Trial - Mahboubeh Firouz; Narjes Noori; Marzieh Ghasemi; Alireza Dashipour; Narjes Keikha (Tehran University of Medical Sciences, 2020)
Objective: Intrauterine insemination (IUI) is an assisted conception technique that involves the deposition of a processed semen sample in the upper uterine cavity, overcoming natural barriers to sperm ascent in the female reproductive tract. Hence, we compared the results of doing intra-uterine insemination 36 and 42 hours after human chorionic gonadotropin (hCG) hormone injection to achieve clinical and chemical pregnancy rates. Materials and methods: One hundred and sixty infertile women with unexplained infertility participated in this clinical trial. They were divided into two groups: those who underwent IUI 36 hours after hCG injection (control group), and those who underwent IUI 42 hours after hCG injection (case group). Statistical analyses were done using IBM-SPSS 25.0. and Chi-square test were used for data analysis. Results: The percentages of clinical and chemical pregnancies were significantly higher in the 42h group compared to the other group (P = 0.038 vs. P = 0.009, respectively). There was no significant difference regarding frequency of abortion, twin and ectopic pregnancies between the two groups (P > 0.05). Conclusion: Doing IUI 42 hours after hCG injection can significantly increase chances of fertility compared to doing it 36 hours after hCG injection.